DAMPAK ARTIFICIAL INTELLIGENCE TERHADAP PERKEMBANGAN LAPANGAN PEKERJAAN DI KOTA JAKARTA TIMUR TAHUN 2020–2022 (LITERATURE REVIEW) - Zikriah, Zikriah (Journal of Engineering, Technology and Computing (JETCom), 2023)
This study reveals that the development of Artificial Intelligence (AI) has a significant impact on the job market in East Jakarta during the period of 2020–2022. AI has positive effects, such as the creation of new jobs in the technology sector and increased efficiency in several industries. However, AI also leads to job reductions in sectors dependent on manual and routine labor. Sectors such as manufacturing, banking, and retail are among the most affected by automation and digitalization triggered by AI. Furthermore, there are challenges related to workforce skill gaps, which require reskilling and upskilling to adapt to the new labor market demands. Therefore, inclusive policies and training programs are needed to ensure that the workforce in East Jakarta can compete in this technological era.